Mental health in mariel cubans and haitian boat people - Eaton, W. W.; Garrison, Roger H.
tbls.
pp. 1395-1415
Keywords: Inmigrantes; Cubanos; Haitianos; Estados Unidos de America; Salud Mental; Refugiados; Alcoholismo